STATIC PROPERTIES OF THE 6Li NUCLEUS IN THE THREE-CLUSTER MODEL - Баяхметов, Олжас; Sakhiyev Саябек; Pomerantsev Владимир (Bulletin of Abai KazNPU. Series of Physical and Mathematical sciences, 2021)
This scientific work is devoted to a deep study of the structure of the weakly bound light 6Li nucleus in the framework of the three-cluster α+p+n-model. The realistic Reid soft core potential (RSC-potential) have been utilized as the nucleon-nucleon interaction. The potential with even-odd splitting in waves is used for describing the interaction of the alpha-particle and nucleons. The spectrum of low-lying energy levels of the 6Li nucleus has been calculated, and realistic wave functions of the relative motion of the clusters in this nucleus have been defined. The matrix elements and operators of the main static characteristics of the 6Li nucleus are presented. In particular, the root-mean-square charge and material radii, magnetic dipole and electric quadrupole moments of the 6Li nucleus have been calculated.